Indonesia Etnostem dan Literasi Nutrisi: Memetakan Tren dan Perspektif Penelitian tentang Zat Makanan melalui Bibliometrik - Kurnia, Fitri Hayati; N, Ade Yeti; Agustina, Tri Wahyu (Publikasi Penelitian Terapan dan Kebijakan, 2024)
Global health and nutrition issues highlight the importance of nutritional literacy, which involves understanding food substances and making appropriate dietary decisions. The Ethnostem approach, integrating local knowledge with science, technology, engineering, and mathematics (STEM), is expected to provide a comprehensive perspective on nutritional literacy. This study aims to map trends and perspectives in food substance research through bibliometrics, focusing on Ethnostem and nutritional literacy. The method used is a literature review with keywords 'ethnostem food testing nutritional literacy' via Publish or Perish and Google Scholar, covering publications from 2018 to 2024, and analysis using VOSviewer. Results indicate a significant increase in publications on nutritional literacy and Ethnostem, particularly in 2023. Bibliometric analysis identifies key clusters, such as the application of Ethnostem education, integration of scientific literacy with indigenous knowledge, and the use of technology in ethno-science education. Data visualization shows interconnections and the temporal evolution of this research. In conclusion, integrating Ethnostem into nutritional education enriches teaching methods and enhances nutritional literacy, emphasizing the need to bridge traditional and modern scientific knowledge for a holistic understanding of nutrition. Further efforts are needed for the practical implementation of ethno-STEM in scientific literacy curricula to improve understanding and health.